A microstructure-dependent plate model for orthotropic functionally graded micro-plates. Issue 14 (18th July 2019) - Zihao, Yang; He, Dan
ABSTRACT: A microstructure-dependent plate model for bending of orthotropic functionally graded micro-plates was proposed on the basis of a re-modified couple stress theory. The proposed model contributed a consideration of micro- as well as macroscopic anisotropy of the plate. Meanwhile these two category material attributes are also assumed to vary continuously through the thickness direction by a power law. From a detailed process of variation the equilibrium equations and related boundary conditions are derived. A simply supported square plate subjected to a double sinusoidal distributed load is taken as the illustrative example and analytically solved. Numerical results demonstrated that the developed micro-plate model predict smaller deflections and stresses than classical model. In addition, the magnitudes of additional bending stiffness in two orthogonal directions caused by scale effect are different.